Air Pollution Associated with Total Suspended Particulate and Particulate Matter in Cement Grinding Plant in Vietnam - Tinh Thai; Ales Bernatik; Petr Kučera (Atmosphere, 2021)
Air pollution associated with suspended particles has become a significant concern in Vietnam recently. The study aimed to (1) investigate dust sources; (2) measure concentration levels of Total Suspended Particulate (TSP), Particulate Matter (PM) fractions; (3) identify silica levels and the correlation with respirable particles at a cement grinding plant in Vietnam. A total of 312 samples (52 TSP, 160 PMs) at 13 processes were measured using the direct-reading dust meter. The silica composition was analyzed in a certified laboratory using the X-ray fluorescence (XRF) technique. SPSS version 26 for Window was used to analyze the data. The operations of the cement grinding plant created multiple dust sources from the jetty to the cement dispatch process. The TSP levels ranged 0.06–38.24 mg m−3, and 40.38% (n = 21) TSP samples exceeded the Permissible Exposure Limit (PEL) for an 8-h working shift. Besides that, there was a wide range and significant concentration levels of PMs in the cement processes. The levels of PMs were PM1 (0.00–0.06 mg m−3), PM2.5 (0.01–0.83 mg m−3), PM4 (0.02–4.59 mg m−3), PM7 (0.03–16.94 mg m−3), and PM10 (0.04–26.85 mg m−3). The highest mean levels of PMs factions were measured at the pre-grinding process. The inefficient operation of the dust collector contributed a significant factor to the dust dispersion in this process. The silica’s mean (SD) composition in respirable dust was 20.4% (0.86) and was not significantly different amongst the processes. There was a significant correlation between the levels of respirable dust and silica exposure in the cement grinding plant (r = 0.99). The improvement of indoor air quality is needed to prevent health effects on cement workers.